Lights and Shadows : The Ongwen Case at the International Criminal Court - Almeida, Fabio Ferraz de,; Perez-Leon-Acevedo, Juan-Pablo, (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2026)
What happens when a former child soldier becomes a convicted war criminal? Lights and Shadows of the Ongwen Case at the International Criminal Court explores this unique and controversial trial - arguably the most complex in ICC history. Learn how law, culture, gender, and justice collide through insights from legal scholars, anthropologists, and sociologists. From charges of forced marriage to the role of spiritual duress, and from local Acholi justice practices to the lives of children born of war, this edited collection uncovers some of the difficult questions international criminal law must face. A must-read for anyone seeking to understand the challenges of international criminal justice in action.